Identification of an SCF ubiquitin–ligase complex required for auxin response in Arabidopsis thaliana - Gray, William M. (Cold Spring Harbor Laboratory Press, 1999)
The plant hormone auxin regulates diverse aspects of plant growth and development. We report that in Arabidopsis, auxin response is dependent on a ubiquitin-ligase (E3) complex called SCF(TIR1). The complex consists of proteins related to yeast Skp1p and Cdc53p called ASK and AtCUL1, respectively, as well as the F-box protein TIR1. Mutations in either ASK1 or TIR1 result in decreased auxin response. Further, overexpression of TIR1 promotes auxin response suggesting that SCF(TIR1) is limiting for the response. These results provide new support for a model in which auxin action depends on the regulated proteolysis of repressor proteins.